2010
DOI: 10.1051/0004-6361/201014817
|View full text |Cite
|
Sign up to set email alerts
|

WASP-21b: a hot-Saturn exoplanet transiting a thick disc star

Abstract: We report the discovery of WASP-21b, a new transiting exoplanet discovered by the Wide Angle Search for Planets (WASP) Consortium and established and characterized with the FIES, SOPHIE, CORALIE and HARPS fiber-fed echelle spectrographs. A 4.3-d period, 1.1% transit depth and 3.4-h duration are derived for WASP-21b using SuperWASP-North and high precision photometric observations at the Liverpool Telescope. Simultaneous fitting to the photometric and radial velocity data with a Markov Chain Monte Carlo procedu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
52
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
2

Relationship

6
4

Authors

Journals

citations
Cited by 54 publications
(68 citation statements)
references
References 28 publications
16
52
0
Order By: Relevance
“…The smallest massive planet HAT-P-20b (Bakos et al 2010) orbits a host star with the strongest metallicity index [Fe/H] = 0.35. On one hand, this follows the trend observed at lower masses that planets around metal-rich stars contain more heavy elements and are therefore on average smaller (see Guillot 2008;Bouchy et al 2010). On the other hand, one would expect that the atmosphere of KOI-423b is poorer in heavy elements, hence yielding smaller opacities, and potentially, a smaller size.…”
Section: System Parameterssupporting
confidence: 74%
“…The smallest massive planet HAT-P-20b (Bakos et al 2010) orbits a host star with the strongest metallicity index [Fe/H] = 0.35. On one hand, this follows the trend observed at lower masses that planets around metal-rich stars contain more heavy elements and are therefore on average smaller (see Guillot 2008;Bouchy et al 2010). On the other hand, one would expect that the atmosphere of KOI-423b is poorer in heavy elements, hence yielding smaller opacities, and potentially, a smaller size.…”
Section: System Parameterssupporting
confidence: 74%
“…For example the masses of 1000 single stars, derived by Valenti et al (1998) via spectral analysis, were found to be systematically 10% larger than those derived from theoretical isochrones. A similar discrepancy was also found in the analysis of the stellar parameters of WASP-37 (Simpson et al 2011), WASP-39 , and WASP-21 (Bouchy et al 2010). Additionally, different sets of theoretical models might not perfectly agree with each other (Southworth 2010), and moreover at younger ages isochrones are closely packed A73, page 8 of 17 and a small change in T eff or ρ can have a significant effect on the derived stellar age.…”
Section: Stellar Parameterssupporting
confidence: 53%
“…It is very similar to WASP-21b (Bouchy et al 2010), which has a similar mass (0.3 M Jup ), is also bloated (1.2 R Jup ), and also has a 4 day orbit around a G star.…”
Section: Wasp-74mentioning
confidence: 55%